A smart choice for indian business firms - Lourdu initha, S.; Renugadevi, J. (university of Jaffna, 2014)
Cooperation among countries has become a significant component to complement their scarce resources, which in turn, have contributed much to the development of human race and the economy. Therefore in a more globalized world, it becomes essential to be more integrated as it adds meaning and strength to the linkages between countries. This could be possible when countries come closer to one another under the banner of Free Trade Agreement. This paper on the proposed topic explores whether India Singapore Comprehensive Economic Cooperation Agreement (CECA) is the major determinant factor that influence the Indian business firms to consider Singapore a Smart Choice for their business. The study also rekindled the ancient bonds of friendship between India and Singapore and served to highlight the natural strategic imperative for the relationship in contemporary times. It also reinforced the importance of strengthening connectivity in all its dimensions between India and Singapore. The study also shed lights on the progress that has been made in trade in goods, services and investments with the signing of CECA in 2005. It is concluded that implementation of CECA alone does not influence the perceptions of Indian business community. There are other factors such as strategic location, efficient administration system etc., that motivate Indian business community to consider Singapore a favorable export destination. CECA will continue to be a pillar in India-Singapore commercial cooperation. It acts as a bridge for India to reach out to the region.
Keywords: Factors; CECA; Business community; Export destination